Regeneration Potential of Aloe Vera Extract against Streptozotocin Induced Hepatic Damage - Younas, Mubeen; Noor, Kinza; Zahid, Muhammad Ali; Iqbal, Muqaddas; Naz, Noor-e-Saba; Khan, Moha Akram; Awan, Sana Javed (Indus Journal of Bioscience Research, 2025)
Diabetes, a metabolic progressive disorder marked with high blood glucose due to resistance to insulin, insufficient secretion of insulin leading to malfunction of vital organs especially eyes, heart, kidneys, nerves and also blood vessels. The utilization of plants into practice of medicine represents one of the foremost human use of natural world. For the progress of novel pharmaceutical products, ethnomedical remedies propose striking templates which include compounds with pharmacological events, which could be altered into modern therapeutic agents as diabetic supplements, nutraceuticals and phytomedicines. The central purpose inside drug invention and upgrading is the production of safe and effective remedies. Streptozotocin have major contribution in the diabetes. STZ can cause different severity of diabetes according to selected dose and type of animal. Diabetes mellitus is growing to epidemic proportion, which cause complications if not treated properly. Although there are many anti diabetic medicines which have different mechanisms to control or treat diabetes. There are many natural substances which can be used for anti-diabetic effects. Therefore, the use of anti-diabetic agents is helpful in the therapeutic treatment of diabetes. The initiation of diabetes was used for 12 adult Wistar rats weighing between 150-250 grams (75-90 days old). The rats got doze after 16 hours of hunger. The rats were originally treated with nicotinamide (vitamin B3). On day 21 their biochemical parameters, pancreatic tissue and PCR Study of pancreas were determined. There is marked raised in different biochemical parameters. Diabetes Mellitus patients are seriously complicated by liver damage. Insulin resistance has grown into one of the main factors that contribute to liver damage, exacerbated by oxidative stress and aberrant inflammatory signals. Insulin resistance will then lead to chronic and possibly fatal conditions including cirrhosis or liver failure at the end of the cycle. Plant and natural products containing antioxidants with good antidiabetic, anti-inflammatory and anti-glycemic effects will be the treatment of the day. In summary, the loss of insulin in a rats from STZ induced injury leads to activation of cellular apoptotic pathway, increase in oxidative stress and decrease in proliferation thus disturbing the whole liver functions.